小說 『三國志』의 回目變化에 대한 고찰 - 玉珠; Ock Ju; 閔寬東; Min Kwan Dong (중국학보, 2020)
소설 『삼국지』는 平話本 시대를 거쳐 나관중의 ≪三國志通俗演義≫가 나오면서 240則本 시대를 열었다. 이 시기의 판본은 크게 演義系列과 志傳系列의 분류된다. 그 후 다시 120回의 李卓吾批评本 시대를 거쳐 毛宗岗의 통행본시대로 통합되었다. 이렇게 수백 년에 걸친 成書過程에서 소설 『三國志』는 내용은 물론 回目또한 다양한 변화양상을 보이며 진화하였다. 나관중의 240則本이 출간된 이래 江南의 演義系列과 福建의 志傳系列은 매우 치열한 판권경쟁이 이루어지는데 이러한 과정을 통하여 소설 『三國志』의 回目과 내용 등은 크게 변화하였다. 그 후 명말 吳觀明 간행본 『李卓吾先生批評三國志』의 출현은 回目의 발전에 또다른 이정표를 세우며 본격적인 120回本 시대를 열었다. 최후에 모종강은 120回의 기본 틀과 스토리는 그대로 유지한 채 回目과 文體 및 揷入詩 등의 구성 체계를 대폭 수정하여 품격 있고 세련된 소설 『三國志』를 재탄생시켰다. 필자는 嘉靖本·喬山堂本(劉龍田)·李卓吾本·毛宗崗本을 핵심 판본으로 삼아 주로 回目變化에 대한 양상을 총체적 분석해 보았다. 그 결과 다양한 회목변화의 양상을 확인할 수 있었는데 대략 2가지로 귀결된다. 첫째는 내용의 확대에 따른 변화이고, 둘째는 상업성에 근거한 차별화로 치열한 출판경쟁이 그 원인이라 할 수 있다. The novel The Romance of Three Kingdoms evolved into the era of 240 Chik(則, interpretation rules) Yanyi series(演義系列) and Zhizhuan series(志傳系列) by Luo Guanzhong from the era of Pinghwa version(平話本) of 70 Chik at the beginning. Then again, it proceeded through the era of Li Zhuowu Criticism version(李卓吾批评本) of 120 editions(回) to be integrated into the era of The Romance of Three Kingdoms of Mao Zonggang(毛宗岗). As such, during the process of book formation that span over 100 years, the chapter titles(回目) of the novel The Romance of Three Kingdoms also evolved by showing a variety of transformation. Since the publication of collected writings of 240 Chik, by Luo Guanzhong, the contents and chapter titles of the novel The Romance of Three Kingdoms had been drastically renewed based on the severe publication rights competition between Yeoneui series of Jiangnan(江南) and Jijeon series of Fujian(福建), especially during the Ming dynasty. In addition, the emergence of 『Li Zhuowu Criticism version』 of 120 editions(回) published by Wuguanming(吳觀明) at the end of Ming Dynasty established another signpost in the development of the chapter titles. In addition, Mao Zonggang significantly modernized the composition including the chapter titles, styles, and inserted poems while maintaining the story of the 120 veditions(回) as they were, notably increasing the dignity and class of the novel The Romance of Three Kingdoms. As a result of the analysis focusing on chapter titles of the Jiajing version(嘉靖本), the core collected writings, Qiaoshantang version(喬山堂本) of Liu Longtian(劉龍田), Li Zhuowu version, and Mao Zonggang version, the researcher could confirm a variety of transitions. Moreover, there are largely two factors of change of the chapter titles, the first one is the change due to the expansion of contents, and the second factor is the differentiation based on commercial viability.